2022
DOI: 10.3390/ijerph19106177
|View full text |Cite
|
Sign up to set email alerts
|

Disinfecting Action of Gaseous Ozone on OXA-48-Producing Klebsiella pneumoniae Biofilm In Vitro

Abstract: Klebsiella pneumoniae is an emerging multidrug-resistant pathogen that can contaminate hospital surfaces in the form of a biofilm which is hard to remove with standard disinfectants. Because of biofilm resistance to conservative disinfectants, the application of new disinfection technologies is becoming more frequent. Ozone gas has antimicrobial activity but there is lack of data on its action against K. pneumoniae biofilm. The aim of this study was to investigate the effects and mechanisms of action of gaseou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Piletić et al ( 2022 ) also use an ATP luminometer to determine the efficiency of ozone, in the form of gas, on ceramic plates (in vitro) contaminated with Klebsiella pneumoniae and showed that ozone caused a significant reduction in biofilm. Recently, in the COVID-19 pandemic context, Mascarenhas et al ( 2022 ) used an ozonated water spray (0.7–0.9 ppm O 3 ) to disinfect the garments and accessories of a hundred volunteers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Piletić et al ( 2022 ) also use an ATP luminometer to determine the efficiency of ozone, in the form of gas, on ceramic plates (in vitro) contaminated with Klebsiella pneumoniae and showed that ozone caused a significant reduction in biofilm. Recently, in the COVID-19 pandemic context, Mascarenhas et al ( 2022 ) used an ozonated water spray (0.7–0.9 ppm O 3 ) to disinfect the garments and accessories of a hundred volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…In a short report (Breidablik et al 2020), the same researchers showed that ozonated water together with a regular soap-and-water hand wash may be more effective than alcohol for the removal of bacteria from artificially contaminated hands. Piletić et al (2022) also use an ATP luminometer to determine the efficiency of ozone, in the form of gas, on ceramic plates (in vitro) contaminated with Klebsiella pneumoniae and showed that ozone caused a significant reduction in biofilm. Recently, in the COVID-19 pandemic context, Mascarenhas et al (2022) used an ozonated water spray (0.7-0.9 ppm O 3 ) to disinfect the garments and accessories of a hundred volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our findings confirm high ozone efficacy against airborne bacteria in hospital settings reported earlier ( 25 ). However, its application as ambient disinfectant has certain limitations, as ozone gas it toxic to humans and can affect the respiratory system ( 41 ). The Croatian standards limit its concentration to 0.39 mg/m 3 over no more than 8 h a day ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…strains, but found that ozone was unable to eradicate the pre-formed biofilm. Moreover, Piletić et al 28 reported that 25 ppm ozone gas could reduce biofilm but did not wholly eradicate the K. pneumoniae biofilm formed on ceramics.…”
Section: Discussionmentioning
confidence: 99%